Analysis of Solving Physics Problems Using the Minnesota Model for Mechanics Concepts - Muhammad Syukri; Elva Sesioria Putri; Musdar Musdar; Lilia Halim (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The purpose of this study is to analyze students' ability to solve physics problems in mechanical materials using the Minnesota problem-solving model. The research method used is descriptive qualitative research. The population in this study is class XI IPA MAN I Banda Aceh students with 10 subjects. The instrument in this study uses a description test with 5 questions. The results of this study are shown to analyze the process of students in solving physics problems that require a high level of thinking, the way students understand concepts, describe problem situations, plan solutions, carry out solutions and evaluate answers. Based on the results of the study, the average student could use the Minnesota problem-solving model in answering physics questions and using this model students are skilled at selecting relevant information, then analyzing it and finally re-researching the results.